Odpowiedzi

Najlepsza Odpowiedź!
2010-04-09T17:36:03+02:00
X+2y-(x-5)(y+2)
x+2y-(xy+2x-5y-10)
x+2y-xy-2x+5y+10
-x+7y-xy+10

14x+3(x+2y)-4(y-0,25x)
14x+3x+6y-4y+x
18x+2y

(1,5-6x)=-3(2+x)
1,5-6x=-6-3x
-6x+3x=-6-1,5
-3x=-7,5/:(-3)
x=2,5

(x+1)(x+2)=x(x+1) +3
x²+2x+x+2=x²+x+3
x²+2x+x-x²-x=3-2
2x=1/:2
x=0,5

Myślę, że pomogłam ;)
Pozdro.
1 5 1
2010-04-09T17:45:41+02:00
X+2y-(x-5)(y+2)=x=2-xy-2x+10+5y=-x+7y-xy+10

14x+3(x+2y)-4(y-0,25x)=14x+3x+6y-4y+x=18x+2y

(1,5-6x)= -3(2+x)=(1,5-6x)=-6-3x

(x+1)(x+2) = x(x+1)+3=x(x+1)+3=x²+2x+x+2=x²+x+3=x²+3x+2=x²+x


1 3 1